Altered xanthophyll compositions adversely affect chlorophyll accumulation and nonphotochemical quenching in Arabidopsis mutants - Pogson, Barry J. (The National Academy of Sciences, 1998)
Collectively, the xanthophyll class of carotenoids perform a variety of critical roles in light harvesting antenna assembly and function. The xanthophyll composition of higher plant photosystems (lutein, violaxanthin, and neoxanthin) is remarkably conserved, suggesting important functional roles for each. We have taken a molecular genetic approach in Arabidopsis toward defining the respective roles of individual xanthophylls in vivo by using a series of mutant lines that selectively eliminate and substitute a range of xanthophylls. The mutations, lut1 and lut2 (lut = lutein deficient), disrupt lutein biosynthesis. In lut2, lutein is replaced mainly by a stoichiometric increase in violaxanthin and antheraxanthin. A third mutant, aba1, accumulates normal levels of lutein and substitutes zeaxanthin for violaxanthin and neoxanthin. The lut2aba1 double mutant completely lacks lutein, violaxanthin, and neoxanthin and instead accumulates zeaxanthin. All mutants were viable in soil and had chlorophyll a/b ratios ranging from 2.9 to 3.5 and near wild-type rates of photosynthesis. However, mutants accumulating zeaxanthin exhibited a delayed greening virescent phenotype, which was most severe and often lethal when zeaxanthin was the only xanthophyll present. Chlorophyll fluorescence quenching kinetics indicated that both zeaxanthin and lutein contribute to nonphotochemical quenching; specifically, lutein contributes, directly or indirectly, to the rapid rise of nonphotochemical quenching. The results suggest that the normal complement of xanthophylls, while not essential, is required for optimal assembly and function of the light harvesting antenna in higher plants.